Synchronous Vs. Asynchronous Online Language Learning Post-Covid-19 - Pardede, Parlindungan; Angelianawati, Luh (Faculty of Letters, Universitas Abdurachman Saleh Situbondo, 2024)
The concepts of EFL learners’ perceptions of online learning in current literature were generated by research conducted before and amid the COVID-19 pandemic. Due to the different status of online learning post-COVID-19, these concepts might have been unfashionable. This explanatory sequential mixed methods study aimed to uncover pre-service EFL teachers’ perceptions of asynchronous online learning (AOL) and synchronous online learning (SOL) post-COVID-19 pandemic to fill in the gap. Involving 34 pre-service EFL teachers at Universitas Kristen Indonesia, data were collected and triangulated using a survey and a semi-structured interview. The results revealed that the participants had positive perceptions of AOL and SOL. However, their perception of AOL was higher in terms of engagement, interaction, collaboration, and advantages than that of SOL. The latter was higher only in social presence, indicating the AOL’s superiority over SOL. The participants also believed that, if designed well and supported by high-quality tools, an internet connection, and bandwidth, both AOL and SOL can facilitate a robust learning environment for EFL learning and teaching. Thus, future research should focus on instructional designs of both AOL and SOL (or their combination) that can optimize their power for delivering learning materials and experiences.